Clinical and Radiographic Alterations in Bilateral Avascular Necrosis of the Femoral Head Following Laser Acupuncture: A Case Report - Jafarian, Ali Akbar; Farhoodi, Ali; Momeni, Mahnoush; Babaei, Mohammad Reza; Kazemi khoo, Nooshafarin (Journal of Lasers in Medical Sciences, 2018)
Introduction: Avascular necrosis (AVN) of the femoral head is an increasingly common cause of musculoskeletal disability with unknown etiology. Traumatic and non-traumatic factors can be effective in its occurrence. About 50% of cases are bilateral. The underlying treatment is prosthetic replacement surgical procedure. Case Presentation: We report a case of bilateral AVN of femoral heads who was a candidate for prosthetic replacement surgery but improved significantly, using laser acupuncture. The patient was a 55-year-old woman with a diagnosis of bilateral osteonecrosis of the femoral head for five years. As the patient declined the surgical option, laser acupuncture was started for pain control. Regarding the signs of bilateral femoral head recovery (according to the MRI scan criteria), a total of 3 courses of laser acupuncture (each course was 20 sessions) with 2 months intervals was performed. Ten acupuncture points: Li4, Li11, St36, SP6, LIV3, GB4, GB5, GB6, GB13, GB14, GB20, GB30, GB31, GB34, were irradiated bilaterally using red 650 nm laser, 100 mW, 1505 Hz frequency, duty cycle 50 3 J/point and near infrared 810 nm laser, 100 mW, 1705 Hz frequency, duty cycle 50 3 J/point, for 2 minutes. The patient received 3 laser therapy courses. During the first-course, laser therapy was done every other day to reduce pain. For the second and third courses, according to pain decrease, therapy was done every week. Results: The results of the MRI scans and x-ray studies show progressive regeneration of the right femoral head from VI to B II and of the left from V to C II (based on the standard table of Pennsylvania). Conclusion: It seems that this procedure may be mentioned in future research projects, especially in cases with high risks of surgery.